Patterns of vagrancy and long-distance dispersal in migratory birds - Zawadzki, LC (2021)
Vagrancy, the process in which organisms travel far outside of their known species’ breeding and wintering range, has long been thought to be an aberrant trait. Vagrants are hypothesised to result from a series of individual mistakes, such as inheritance of an incorrect compass bearing, or displacement by wind or weather systems. Though previous studies on vagrancy do not provide sufficient evidence to support these hypotheses, vagrancy still remains understudied. This thesis uses a combination of experimental field techniques, and indirect methods, to study how and why vagrancy occurs in migratory birds. More specifically, I investigated whether vagrants differ behaviourally from non-vagrants, and what factors drive vagrant occurrence. Firstly, I tested the orientation behaviour of vagrant and non-vagrant passerines to determine whether vagrants are capable of selecting a preferred migratory bearing. That is, are vagrants capable of initiating directed migratory flights? I found that not only do vagrants select a preferred orientation, but that orientation did not significantly differ from that of our non-vagrant control species, the Blackpoll Warbler (Setophaga striata). Both vagrants and non-vagrants oriented on a north/northwesterly heading, which is consistent with studies on post-fledging exploration of Blackpoll Warblers. This suggests that vagrancy may be linked to post-fledging exploration. Feathers from these vagrants were also assessed for the ratio of stable-hydrogen isotope (deuterium; δ2H) to pinpoint their natal origin. The majority of vagrants were found to originate from the edge of their breeding range, which has been associated with increased exploratory behaviour in other species of passerines. External factors that may drive vagrant occurrence were also examined. For vagrant New World warblers, the size of the overall breeding population and vagrant distance were found to best predict vagrancy. Furthermore, when examined at the regional level, each species was best predicted by the annual variation in population size and growth at the edge of their breeding range, supporting my results that vagrants originate along the range edge. Additionally, this relationship was negative, suggesting quadratic density-dependence, whereby vagrants irrupt in years of plentiful resources as the population increases, and erupt in years of depleting resources, when the population exceeds available food or habitat. I tested whether this relationship could be used to infer the source population of vagrants indirectly, using vagrant Lesser Black-backed Gulls (Larus fuscus). Though it was possible to infer their origin, increased survey efforts are needed to improve predictions. Finally, since vagrants are irruptive, I investigated irruptions in the Northern Saw-whet Owl (Aegolius acadicus) to determine drivers of irruption cycles in this species. Irruptions were strongly influenced by prey abundance, which suggests that vagrants may respond to food availability. Overall, this thesis challenges the idea that vagrants are aberrant, and instead suggests that this behaviour is within the scope of the normal migratory programme.